Phytoremediation potential of indoor plants in reducing air pollutants - Ravindra, Khaiwal; Mor, Suman (Frontiers in Sustainable Cities, 2022)
Indoor air quality (IAQ), specifically after the COVID-19 pandemic, has become an international issue, as humans spend 80–90% of their time in indoor microenvironments. Poor IAQ has been related to the sick-building syndrome, nasal and ocular irritations, allergies, and respiratory dysfunction, including premature deaths. Phytoremediation is a novel strategy to absorb, adsorb, assimilate or transfer/reduce air pollutants and improve the IAQ using plants. Hence, the current review aims to explore indoor plants' role in improving indoor air quality, including their purification capabilities. There is increasing evidence that various plant species (e.g., Ficus benjamina, Chlorophytum comosum, Draceana) or their parts can reliably reduce the concentration of numerous air pollutants in the indoor microenvironment and promote human wellbeing. However, the indoor air pollutants removal efficiency depends on the species of plant, various plant characteristics such as leaf size, thickness, area, photosynthetic activity, light intensity and part of plant involved, i.e., roots, leaves, wax, cuticle and stomata. Using indoor plants is one of the most cost-effective and reliable methods of making a healthier indoor environment. Better public health can be maintained at a lower cost, with less strain on the health care system, if more emphasis is placed on creating a biophilic atmosphere and increasing the use of indoor plants. However, there are no established criteria for the best indoor plants and the impact of indoor plants on various factors such as interior ventilation, temperature, humidity, etc. Therefore, further experimental research is needed that simulates the interior environment to monitor the impacts of indoor plants on factors such as humidity, temperature, ventilation, etc., in improving the microenvironment of a closed space/room.